Correlation Between Proton Pump Inhibitors and the Complications of Liver Cirrhosis: A Systematic Review and Meta-Analysis - Seong Jun Hwang; Dong Hyeon Lee; Seong-Joon Koh; Seong-Joon Koh; Ji Won Kim; Ji Won Kim; Hyun Sun Park; Hyun Sun Park; Byeong Gwan Kim; Kook Lae Lee (Turkish Journal of Gastroenterology, 2022)
Background: Many studies and meta-analyses have investigated the associations among proton pump inhibitors (PPIs), spontaneous bacterial peritonitis (SBP), portosystemic encephalopathy (PSE), and other infections. However, these studies had limitations, including the omission of several relevant studies and drawing conclusions, based on the abstracts without consulting the full-text of the articles. To evaluate the association between PPIs and complications arising from cirrhosis and risks of PPI use in patients with cirrhosis.Methods: Data were extracted from the EMBASE, PubMed, Cochrane, and Google Scholar databases. The Newcastle-Ottawa scale was used to assess the quality of the selected studies.Results: A total of 29 studies (13 case–control and 16 cohort studies) involving 20,484 patients were included in the meta-analysis. The total relative risk (RR) for the 23 studies which investigated SBP was 1.31, and the 95% CI was 1.10-1.55 (I2 = 73.0%). The total RR for the 7 studies which examined PSE was 1.25 (95% CI 0.85-1.84, I2 = 96.1%). For the 7 studies which analyzed overall infection, the total RR was 1.37 (95% CI 1.07-1.76, I2 = 79.3%). The RR for the 2 cohort studies that assessed mortality was 1.39 (95% CI 0.85-2.27, I2 = 0.0%).Conclusion: PPI use in cirrhosis patients increased the SBP and overall infection risk. PPIs should be considered with appropriate indications when the benefits exceed the risks in cirrhosis patients with ascites.Cite this article as: Hwang SJ, Lee DH, Koh SJ, et al. Correlation between proton pump inhibitors and the complications of liver cirrhosis: A systematic review and meta-analysis. Turk J Gastroenterol. 2022; 33(1): 44-52.